2018
DOI: 10.4049/jimmunol.1701773
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus Nonstructural Protein 4 Cleaves Porcine DCP1a To Attenuate Its Antiviral Activity

Abstract: As one of the most significant etiological agents in pigs, porcine reproductive and respiratory syndrome virus (PRRSV) has adversely impacted the global swine industry since it was discovered in the 1980s. The mRNA-decapping enzyme 1a (DCP1a), a regulatory factor involved in removing the 5'-methylguanosine cap from eukaryotic mRNA, has recently been identified as an IFN-stimulated gene. However, the role of DCP1a in PRRSV infection is not well understood. In this study, overexpression and knockdown of porcine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
(71 reference statements)
0
15
0
1
Order By: Relevance
“…Our previous study showed that porcine reproductive and respiratory syndrome virus (PRRSV) nsp4 cleaves pDCP1A but not the human or monkey DCP1A homolog (68). Contrary to the species-specific cleavage mediated by PRRSV nsp4 at residue E238 of pDCP1A, residue Q343 and the peptide nearby are quite conserved among different mammalian species of DCP1A, providing a natural substrate for CoV nsp5.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study showed that porcine reproductive and respiratory syndrome virus (PRRSV) nsp4 cleaves pDCP1A but not the human or monkey DCP1A homolog (68). Contrary to the species-specific cleavage mediated by PRRSV nsp4 at residue E238 of pDCP1A, residue Q343 and the peptide nearby are quite conserved among different mammalian species of DCP1A, providing a natural substrate for CoV nsp5.…”
Section: Discussionmentioning
confidence: 97%
“…PRRSV Nsp4 has inhibitory effects on IFN-β, NF-κB, and IRF3, thus suppressing the host’s innate immune mechanism ( Chen et al, 2014 ). Moreover, Nsp4 can proteolytically cleave the host’s antiviral genes to antagonize antiviral activity, such as NF-κB essential modulator (NEMO), zinc finger antiviral protein (ZAP), mRNA-decapping enzyme 1a (DCP1a), and virus-induced signaling adaptor (VISA; Huang et al, 2016 ; Tao et al, 2018 ; Chen et al, 2019 ; Zhao et al, 2020 ). Considering the proteolytic enzyme activity of Nsp4, the decrease in PKR protein is possibly caused by the cleavage of Nsp4.…”
Section: Discussionmentioning
confidence: 99%
“…However, hCH25H showed greater antiviral activity against PRRSV, compared with pCH25H. Recently, our group showed that the PRRSV 3C-like proteinase nsp4 cleaves porcine mRNA-decapping enzyme 1a (pDCP1a), an ISG (60). Human and monkey DCP1a were not be cleaved by PRRSV nsp4, however, because the cleavage site at Glu237 in pDCP1a is substituted with Asp in the human and monkey orthologues.…”
Section: Discussionmentioning
confidence: 99%